Synthesis and Bisazo Acid Dyes Based on 4-Hydroxy-1-Phenylquinoline-2(1H)-one System and Their Dyeing Performance on Various Fabrics - Patel, N.C.; Mehta, A.G. (Asian Journal of Chemistry, 2010)
Fifteen 3-(4' -R-azo-1' -pheny1azo )-4-hydroxy-1-phenylquinolin- 2(1H)-ones (IVa-o) were prepared by coupling diazotised 3-(4'amino- 1' -phenyl azo)-4-hydroxy-1-phenyl quinoline-2(1H)-one (III) with various coupling components (a-o). The compound (I) was coupled with diazotised 4-aminoacetanilide giving compound (II). which on hydrolysis gave compound (III): The compounds (IVa-o) were characterised by elemental and spectral analyses and their .dyeing performance on silk, wool and nylon fabrics was assessed.